Charles Sanders Pierce's Classification of the Sciences: History, Content and Significance - Viet Hung, Le (VNU Journal of Science: Policy and Management Studies; Vol 36 No 1, 2020)
This paper articulates the historical context, systematize, gives out critical judgments, contributes to the improvement of Pierce’s classification of sciences and suggests the benefits and application of Pierce in the theory of science, management, and policy of science. Research methods include: literature reviewing of original papers of Pierce and secondary literature of other scholars; logic analysis examines the internal coherence of Pierce’s classification, historical method puts Pierce’s classification in scientific, historical and sociological context to clarify its origin. The paper outlines reasons and importance for investigation in the introduction; then it outlines the history of pre-Pierce scientific classification, analyses macro- and micro-historical circumstances leading to the introduction of Pierce’s classifications, the content of Pierce's classifications and their significance for culture, scientific research, and scientific research management.